2020
DOI: 10.1103/physrevapplied.13.044075
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Properties, and Applications of Pulsed Laser Deposited Nanolaminate Ti3AlC2 Thin Films

Abstract: Recently, nanolaminated ternary carbides have attracted immense interest due to the concomitant presence of both ceramic and metallic properties. Here, we grow nanolaminate Ti3AlC2 thin films by pulsed laser deposition on c-axis-oriented sapphire substrates and, surprisingly, the films are found to be highly oriented along the (103) axis normal to the film plane, rather than the (000l) orientation. Multiple characterization techniques are employed to explore the structural and chemical quality of these films, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 48 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…In general, three main ion-plasma PVD methods are used to synthesize MAX phase thin films: magnetron sputtering (MS) , cathodic arc deposition (CAD) [112][113][114][115][116][117][118], and pulsed laser deposition (PLD) [119][120][121][122][123][124][125]. Sometimes a combination of methods is used [126][127][128][129][130][131][132].…”
Section: Features Of Pvd Synthesis Methodsmentioning
confidence: 99%
“…In general, three main ion-plasma PVD methods are used to synthesize MAX phase thin films: magnetron sputtering (MS) , cathodic arc deposition (CAD) [112][113][114][115][116][117][118], and pulsed laser deposition (PLD) [119][120][121][122][123][124][125]. Sometimes a combination of methods is used [126][127][128][129][130][131][132].…”
Section: Features Of Pvd Synthesis Methodsmentioning
confidence: 99%
“…There are many kinds of high-temperature solid lubricants such as metal oxides, metal sulfides, inorganic borates and rare earth compounds [10,11]. However, most of the solid lubricants are based on the layered structure materials with weak interlayer forces, for instance, graphite, molybdenum disulfide (MoS 2 ), polytetrafluoroethylene (PTFE), h-BN, etc.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Having an ohmic contact at the interface is most crucial for high-performance digital electronic devices. 18 There are several conceptual and experimental challenges to make a high-quality contact interface for atomically thin 2D SCs, where the depletion and transfer length are smaller. Recently, Shen et al reported ultralow contact resistance between Bi which is a semimetal (SM) and transition-metal dichalcogenides (TMDs).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The semiconductor/metal (SC/M) contact is known to play a crucial role at the interface. The presence of large contact resistance at the 2D SC and 3D metals lowers the device performance. , Having an ohmic contact at the interface is most crucial for high-performance digital electronic devices . There are several conceptual and experimental challenges to make a high-quality contact interface for atomically thin 2D SCs, where the depletion and transfer length are smaller.…”
Section: Introductionmentioning
confidence: 99%